SWOG 1318: A Phase II Trial of Blinatumomab Followed by POMP Maintenance in Older Patients With Newly Diagnosed Philadelphia Chromosome–Negative B-Cell Acute Lymphoblastic Leukemia. Issue 14 (10th May 2022) - Advani, Anjali S.; Moseley, Anna; O'Dwyer, Kristen M.; Wood, Brent L.; Fang, Min; Wieduwilt, Matthew J.; Aldoss, Ibrahim; Park, Jae H.; Klisovic, Rebecca B.; Baer, Maria R.; Stock, Wendy; Bhave, Rupali R.; et al.
Abstract : PURPOSE: Chemotherapy outcomes in older patients with Philadelphia (Ph) chromosome–negative B-acute lymphoblastic leukemia (ALL) are very poor. Here, we evaluated blinatumomab as induction and consolidation therapy followed by prednisone, vincristine, 6-mercaptopurine, and methotrexate (POMP) maintenance chemotherapy in this patient population. PATIENTS AND METHODS: Patients were treated at National Clinical Trial Network sites. Eligibility criteria included age ≥ 65 years and newly diagnosed Ph chromosome–negative B-ALL. Patients received blinatumomab as induction for one-two cycles until attainment of response (complete remission (CR) and CR with incomplete count recovery). Patients then received three cycles of consolidation with blinatumomab followed by 18 months of POMP maintenance chemotherapy. Eight doses of intrathecal methotrexate were administered as central nervous system prophylaxis. RESULTS: Twenty-nine eligible patients were enrolled. The median age was 75 years, and the median bone marrow blast count at diagnosis was 87%. Cytogenetic risk was poor in 10 patients (34%), and five of 14 patients (36%) tested had the Ph-like ALL gene signature. Nineteen patients (66%; 95% CI, 46 to 82) achieved CR. Kaplan-Meier 3-year disease-free survival and overall survival estimates were 37% (95% CI, 17 to 57) and 37% (95% CI, 20 to 55), respectively. CONCLUSION: Blinatumomab was well tolerated and effective in the treatment of older patients with newly diagnosed Ph chromosome–negative B-ALL, including patients with poor-risk cytogenetics. The 3-year disease-free survival and overall survival results are encouraging and suggest that this approach should be further explored.